ANALSIS KECENDERUNGAN PENERIMAAN OPINI AUDIT GOING CONCERN STUDI EMPIRIS PADA PERUSAHAAN PROPERTI YANG TERDAFTAR DI BEI TAHUN 2016-2018 - R. M. Arnaldo Simbolon (2020)
Responsibilities of auditors currently do not only focus on assessing the fairness of financial statements and detecting fraud, but also assess the company's ability to maintain its survival". "This is due to the demands of the shareholders to the auditor to provide early warning about the prospects of a company as consideration before deciding on an investment decisionThis study aims to determine the effect of financial distress, debt default, and company size on going concern audit opinion". This research uses quantitative research methods. This research data uses secondary data through documentation and literature studies. "The population in this study are property companies listed on the Indonesia Stock Exchange in 2016 - 2018". "The sample in this study amounted to 171 observational data from 57 companies selected using the purposive sampling method". "The analysis used in this study is logistic regression analysis At the 5% significance level". "The results of hypothesis testing show that financial distress and company size do not affect going concern audit opinion, while debt default has a significant positive effect on going concern audit opinion".